2012
DOI: 10.1523/jneurosci.0799-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Semaphorin 4D/Plexin-B1-Mediated M-Ras GAP Activity Regulates Actin-Based Dendrite Remodeling through Lamellipodin

Abstract: Semaphorins have been identified as repulsive guidance molecules in the developing nervous system. We recently reported that the semaphorin 4D (Sema4D) receptor Plexin-B1 induces repulsion in axon and dendrites by functioning as a GTPase-activating protein (GAP) for R-Ras and M-Ras, respectively. In axons, Sema4D stimulation induces growth cone collapse, and downregulation of R-Ras activity by Plexin-B1-mediated GAP activity is required for the action. Axonal R-Ras GAP activity downregulates phosphatidylinosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 44 publications
1
42
0
Order By: Relevance
“…Lpd has been identified as an M-Ras effector protein but retains a moderate Rap1-binding affinity owing to an RA-PH functional module highly similar to that of RIAM (Lafuente et al, 2004; Tasaka et al, 2012; Yoshikawa et al, 2007; Zhang et al, 2014). Lpd also possesses all R8-interacting residues in RIAM TBS1 in its N-terminal talin-binding site (Lpd-TBS) except a single substitution of Leu15 RIAM with Trp31 Lpd (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lpd has been identified as an M-Ras effector protein but retains a moderate Rap1-binding affinity owing to an RA-PH functional module highly similar to that of RIAM (Lafuente et al, 2004; Tasaka et al, 2012; Yoshikawa et al, 2007; Zhang et al, 2014). Lpd also possesses all R8-interacting residues in RIAM TBS1 in its N-terminal talin-binding site (Lpd-TBS) except a single substitution of Leu15 RIAM with Trp31 Lpd (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While direct binding of the Lpd RA domain to Ras (K-Ras) was not detected in yeast two-hybrid or in vitro binding experiments [17], pull-down assays suggested that Lpd can associate with activated K-Ras, NRas, H-Ras, and R-Ras [82] as well as M-Ras and is required for M-Ras-mediated neuronal 15 dendrite remodeling [83]. The PH domain of Lpd was found to specifically bind to PI(3,4)P2, but not other phosphoinositides (see discussion below).…”
Section: Molecular Structurementioning
confidence: 99%
“…In growth cones, EnaH/VASP proteins are concentrated at filopodia tips (Lebrand et al 2004). EnaH/VASP complex is also required for dendrite growth (Tasaka et al 2012). EnaH/ VASP proteins at the tips of lamellipodia and filopodia accelerate actin polymerization by their anti-capping and bundling activity , and neurons lacking these proteins fail to form neurites (Kwiatkowski et al 2007).…”
Section: Axon Pathfindingmentioning
confidence: 99%